Prevalence of stress and its associated factors on doctors: a cross-sectional study - Brar, Amrit Pal Singh; Jammu, Roopandeep Singh; Sahni, Priya; Brar, Deepinder Pal Singh (International Journal Of Community Medicine And Public Health, 2025)
Background: Stress is a common and natural part of daily life and its prolonged exposure can lead to very harmful effects on the body. In the modern healthcare workplace, there can be a lot of stressful conditions prevailing in the facilities. This study aimed to study the prevalence of stress and its associated factors among doctors. Methods: The study was a cross-sectional study using stratified sampling technique. Results: In our study population, maximum doctors were in age group of 25-34 (40%), males (60%), unmarried (70%). Moderate (50%) to high stress (30%) levels were found among doctors. Working hours per week, night shifts, sleep deprivation were associated factors. Conclusions: The findings of this study underscore the importance addressing both work-related and personal factors in developing interventions to mitigate stress among medical professionals.